Database of the alumni performance of the Ophthalmology Stricto sensu Postgraduate Program at Escola Paulista de Medicina, UNIFESP - Demetrio, Rosangela (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2020)

(untitled) (Acta Cir Bras)
PURPOSE: To develop a database with social, demographic and professional information of all graduates of the two post-graduate programs in Ophthalmology of EPM-UNIFESP, including their opinions on quality, application, and contribution of the courses received in their professional careers. METHODS: The survey was conducted in the digital and physical archives of the University and by telephone contact. When the graduates’ e-mails were all collected, the electronic questionnaire was applied. The responses were compiled. Descriptive analysis of the results obtained in this cross-sectional study was performed, and analyzed by the authors and by statistical professionals, through Excel graphs. RESULTS: The database suggests that most graduates were born and work in the state of São Paulo. A significant fraction of 66.77% is dedicated to academic work, but only 36.2% hold management positions. Most of them receive amounts of one to 56 minimum wages monthly. The main motivation was to improve their professional careers. CONCLUSION: For post-graduate programs, a database with information of its graduates can elucidate whether the goals were achieved based on the proposed teaching, as well as can generate reflections to improve the quality, the courses expectations and the vision that students have of the University.